Managing the Tourism in the Vladimir Region: New Management System of State Programs - Deren Ivanna; Zemlyanikina Anastasiya (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
A proper management mechanism can catalyze a regional tourism industry based on the new management system of state programs with its innovative solutions in public administration. The article describes an effective mechanism for managing regional tourism based on new approaches to state program management. The authors studied the way the local executive authorities strategize the tourism in the Vladimir Region. The research revealed the factors that affect the managerial solutions aimed at improving the current models of public administration. The analysis of strategic documents also revealed some problems of current strategic approaches in shaping the local tourism policy. A software and project approach could improve the management in the sphere of tourism in the Vladimir Region. The mechanism relies on a unified system of strategic priorities, and state support tools. The feedback comes from a complex system of interaction with local municipal communities and businesses. The new management mechanism will be tested as part of a comprehensive state program on the development of tourism in the Vladimir Region. If it proves effective, it can be applied to the entire management system of government programs in the region.